Overexpression of transcription factor Foxa1 and target genes remediate therapeutic protein production bottlenecks in Chinese hamster ovary cells. Issue 4 (23rd February 2020) - Berger, Audrey; Le Fourn, Valérie; Masternak, Jacqueline; Regamey, Alexandre; Bodenmann, Iris; Girod, Pierre‐Alain; Mermod, Nicolas
Abstract: Despite extensive research conducted to increase protein production from Chinese hamster ovary (CHO) cells, cellular bottlenecks often remain, hindering high yields. In this study, a transcriptomic analysis led to the identification of 32 genes that are consistently upregulated in high producer clones and thus might mediate high productivity. Candidate genes were associated with functions such as signaling, protein folding, cytoskeleton organization, and cell survival. We focused on two engineering targets, Erp27, which binds unfolded proteins and the Erp57 disulfide isomerase in the endoplasmic reticulum, and Foxa1, a pioneering transcription factor involved in organ development. Erp27 moderate overexpression increased production of an easy‐to‐express antibody, whereas Erp27 and Erp57 co‐overexpression increased cell density, viability, and the yield of difficult‐to‐express proteins. Foxa1 overexpression increased cell density, cell viability, and easy‐ and difficult‐to‐express protein yields, whereas it decreased reactive oxygen species late in fed‐batch cultures. Foxa1 overexpression upregulated two other candidate genes that increased the production of difficult‐ and/or easy‐to‐express proteins, namely Ca3, involved in protecting cells from oxidative stress, and Tagap, involved in signaling and cytoskeleton remodeling. Overall, several genes allowing to overcome CHO cell bottlenecks were identified, including Foxa1, which mediated multiple favorable metabolic changes that improve therapeutic protein yields. Abstract : In this work, the authors performed a transcriptomic analysis to identify genes upregulated in CHO cells producing therapeutic proteins at high levels. Among them, they identified candidate genes whose overexpression could improve the production of easy‐ and difficult‐to‐express therapeutic proteins. This included Erp27, an endoplasmic reticulum‐located protein that binds unfolded proteins and the Erp57 protein disulfide isomerase, and Foxa1, a pioneering transcription factor whose overexpression upregulated the expression of high production‐associated genes.